The morpho-kinematical structure and chemical abundances of the complex planetary nebula NGC 1514. Issue 4 (30th April 2021) - Aller, A; Vázquez, R; Olguín, L; Miranda, L F; Ressler, M E
ABSTRACT: We present high-resolution, long-slit optical spectra and images of the planetary nebula NGC 1514. The position velocity maps of the [O iii ] emission line reveal complex kinematics with multiple structures. A morpho-kinematical analysis suggests an inner shell, originally spherical and now distorted by several bubbles, and an attached outer shell. The two well-defined, mid-infrared rings of NGC 1514 are not detected in our high-resolution, long-slit spectra, which prevented us from doing a kinematical analysis of them. Based exclusively on their morphology, we propose a barrel-like structure to explain the rings. Several ejection processes have been possibly involved in the formation of the nebula, although a time sequence is difficult to establish with the current data. We also analyse intermediate-resolution, long-slit spectra with the goal of studying the physical parameters and chemical abundances of NGC 1514. The nebular spectra reveal a moderate-excitation nebula with weak emission lines of [Ar iii ], [Ne iii ], He i, and He ii . Neither [N ii ] nor other low-excitation emission lines are detected. We found an electron temperature around 14 000 K in the gas and an electron density in the range of 2000–4000 cm −3 .